AN ASIAN BIBLICAL HERMENEUTICS: PERSPECTIVES AND PROSPECTS - Kalluveettil, Paul (Asian Horizons, 2007)
obody in Asia will disown the relevance for a biblical hermeneutics for this vast continent. There may not be difference of opinion that the Word of God as a consuming fire (Jer.23:29)has not yet touched the soul of Asia. That may be why the majority of its inhabitants remains unaffected at the so-called proclamation of the message of Christ. The Asian Church as a whole does not seem to have made a heart and soul venture towards giving form to an effective method of biblical interpretation, which takes into consideration the existential situation with all its dimensions of the Asian folk. This study does not claim to present such a hermeneutics. The author only wants to invite the attention of the Church leaders to certain foundational factors, on which an authentic Asian hermeneutics can be built.